PBL in HCI Teaching: A case study - Zaphiris, Panayiotis; Arh, Tanja; Klobučar, Tomaž; Pipan, Matija; Ioannou, Andri; Vasiliou, Christina (My University, 2013)
Address problems related to the implementation of PBL pedagogy in higher education - that students are often disengaged from active collaboration, fertile discussion, and physical interaction around emerging group artifacts. focus on design education
Keywords: Human Computer Interaction; Problem Based Learning